THE AGRICULTURE SECTOR IN WESTERN BALKANS – SOME CHARACTERISTICS OF DEVELOPMENT - Nikolić, Radmilo; Fedajev, Aleksandra; Stefanović, Vidoje; Ilić, Silvana (Economics of Agriculture, 2017)
Agriculture in the Western Balkan countries has the signifcant role. It has the highest share in GDP right after the industry. However, transition processes as well as the breakup of former Yugoslavia caused serious stagnation in this economic activity in almost all its areas. Measures and actions taken in order to make an unfavourable situation in this sector better, did not bring results which had been expected. The recovery of agriculture is still slow and faces numerous obstacles. The aim of this paper apropos is to analyse the role of this sector in Western Balkan economies by using the multi-criteria analysis or more precise PROMETHE GAIA methodology. Obtained results indicate that agriculture sector has the most significant role in Albanian economy, followed by FRY Macedonia, Bosnia and Herzegovina, Serbia, Croatia and, at the very end, Montenegro.